Evidenciação de julgamentos, estimativas e premissas contábeis nas demonstrações contábeis de empresas brasileiras - Lima, Janaína Alves (2018)
The accounting estimates and judgments are based on historical experience as well as on other factors such as expectations of future events considered reasonable, thus representing sources of uncertainty with the possibility of relevant changes in the values of assets and liabilities in future years. This research sought to identify the information regarding significant accounting judgments, estimates and assumptions disclosed by Brazilian. For that, a descriptive and qualitative research was carried out, where the Explanatory Notes included in the financial statements of the companies that compose the sample were analyzed. The universe of analysis comprised the five largest companies in eleven sectors and the classification by sector was performed according to the ranking adopted by Revista Exame Maiores e Melhores 2016, totaling 55 companies. The results indicated that the most cited critical estimates were Deferred Income Tax and Social Contribution, Impairment of Fixed Assets and Intangible, Provisions for Civil and Labor Tax Risks and Estimated Losses in Doubtful Settlement Credits. Regarding the sectorial analysis, the results indicated that in some sectors there are similarities and particularities related to critical estimates, but they were not identified in most of them.